Cryptographic Solution-Based Secure Elliptic Curve Cryptography Enabled Radio Frequency Identification Mutual Authentication Protocol for Internet of Vehicles - Surbhi Sharma (IEEE, 2021)
Internet of Vehicles (IoV) is one of the most active research disciplines in Intelligent Transportation Systems (ITS), intending to improve Vehicular Ad-hoc Network (VANET) capabilities. The main objective of IoV is to enhance the safety of passengers by incorporating various advanced information and communication technologies thus, easing the driving experience of passengers and enhancing traffic efficiency. The IoV has numerous key technologies, and one of them is Radio-Frequency Identification Technology (RFID) which has a plethora of applications in IoV like automatic toll collection, intelligent parking, data dissemination, tracking the location of the vehicle, etc. which enhances the overall performance of IoV networks. Along with this, RFID devices are resource-constrained, thus security and privacy are a major concern and also IoV is a real-time sensitive network where security is of utmost importance. Keeping in mind the security perspective, the concept of Elliptic-Curve Cryptography (ECC) is taken into consideration. So, in this paper, we have proposed a Cryptographic solution-based secure ECC-enabled RFID mutual authentication protocol for IoV. The proposed protocol is comprised of three phases: Setup Phase, Tag Authentication Phase, and Server Authentication Phase. Security evaluation of the proposed protocol is performed by taking into consideration the analysis of security requirements as well as security attacks. Also, the simulation of the proposed protocol is done using the AVISPA tool and the results indicate that the proposed protocol is safe against various malevolent attacks. Performance evaluation of the proposed protocol is computed based on parameters i.e., storage requirements, communication cost, and computational cost. Results indicate that the proposed protocol contributes to high performance and security and has low computational cost than other existing authentication protocols. A novel Blockchain-based security framework for RFID-enabled IoV has also been proposed to further enhance the security of the IoV network.